(3cJGH aj GdJaSjQs
(3ChdgG (B:s
(3Chd GdehLhO HOGjI JaSjQ ShQI GdGMbGa hgj ecjI hgj GQHY hKdGKhf GjI hbjd NeS hbGd GHf YWjI s
(3BNQgG (B:s
(3hYf QShd Gddg Udi Gddg Ydjg hSde ef bQC ShQI GdJMQje CJGg Gddg JhHI fUhMkG ced JaSjQgG HMeO Gddg hYhfg s
(3GdehLhO gPG GdLRA ef ShQI GdGMbGa dShQI GdJMQjes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs